(untitled) (Global Journal of Human-Social Science, 2011)
The study aimed to demonstrate the effectiveness of information systems used in Jordanian tourism companies and the quality of services provided by these systems as well as to identify its role in improving the performance of these companies Questionnaires have been distributed to users of the outputs of the information systems section 132 copies were restored valid for statistical analysis The main findings of the study is that the information provided by users in Jordanian tourism businesses is efficient to medium degree except that it does not help to increase the competitiveness of tourist companies there is not enough continuous update for this information and the services provided by the information systems section are of medium quality moreover the training programs offered by the information systems section is not characterized by diversity and innovation and limited to a category without others and does not cover all users from all partitions Information systems improve the performance of the Jordanian tourism companies although it is not flexible to meet changing needs and does not reduce work cycle times nor reduce operations costs and does not contribute to the involvement of employees in decision making Most recommended by Jordanian tourism companies to continuously and sufficiently update the output of the information systems diversification and renewal of training programs offered by the information systems section and cover all users of all departments and increase the flexibility of linking information systems and information systems to reduce work cycle times and reduce processes operation costs